PRIORITAS KEBUTUHAN PELATIHAN PENYULUH PERIKANAN BERBASIS ANALISIS HIERARKI PROSES (AHP) UNTUK MENINGKATKAN KOMPETENSI ERA DIGITAL DI SATMINKAL BPPP MEDAN - Yulya Fitria; Lis M Yapanto; I Ketut Sumandiarsa (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: In the era of Industrial Revolution 4.0 and the transition toward Society 5.0, Indonesia's marine and fisheries sector faces a digital transformation imperative to maintain global competitiveness and resource sustainability. Fisheries extension officers, acting as agents of change, are required to possess adaptive digital competencies to facilitate technology adoption among stakeholders. However, existing training programs are often generic and lack prioritization based on real-world needs and strategic impact. This study aims to map digital competency gaps and formulate strategic training priorities by integrating individual needs with expert perspectives. The research employs a quantitative approach with a two-stage analytical design. A case study was conducted at the Base Administrative Unit (Satminkal) of the Center for Fisheries Training and Extension (BPPP) Medan. In the first stage, a Training Needs Analysis (TNA) was conducted on 230 extension officers to measure digital competency gaps across 12 indicators, followed by a Pareto Analysis to identify critical competencies (the vital few). In the second stage, the five critical competencies identified from the TNA were evaluated by a panel of nine experts using the Analytical Hierarchy Process (AHP) to determine final priorities based on four criteria: urgency, impact on performance, policy alignment, and gap severity. TNA findings revealed the highest gaps in technical competencies: "Operation of Fisheries-Specific Applications" (gap -1.33) and "Digital Content Production" (gap -1.31). Pareto Analysis confirmed that 78.4% of the total gap originated from five vital competencies. AHP results indicated that "Impact on Performance" was the primary determinant (weight 40.1%). The synthesis produced "Operation of Fisheries-Specific Applications" as the top priority (global weight 0.397). The integration of TNA and AHP produces more precise training priorities for effective resource allocation in the digital age.   Keywords: Fisheries Extension Officers; Digital Competence; Training Needs Analysis; Pareto Analysis; Analytical Hierarchy Process   Abstrak: Di era Revolusi Industri 4.0 dan transisi menuju Society 5.0, sektor kelautan dan perikanan Indonesia menghadapi imperatif transformasi digital guna mempertahankan daya saing global dan keberlanjutan sumber daya. Penyuluh perikanan, sebagai agen perubahan, dituntut memiliki kompetensi digital yang adaptif untuk memfasilitasi adopsi teknologi di kalangan pelaku usaha. Namun, program pelatihan yang ada seringkali bersifat umum dan tidak diprioritaskan berdasarkan kebutuhan riil dan dampak strategisnya. Penelitian ini bertujuan untuk memetakan kesenjangan kompetensi digital penyuluh perikanan dan merumuskan prioritas pelatihan yang strategis dengan mengintegrasikan perspektif kebutuhan individu dan pertimbangan ahli. Penelitian menggunakan pendekatan kuantitatif dengan desain analisis bertahap (two-stage quantitative analysis). Studi kasus dilakukan di Satminkal Balai Pelatihan dan Penyuluhan Perikanan (BPPP) Medan. Pada tahap pertama, Training Needs Analysis (TNA) dilakukan terhadap 230 penyuluh untuk mengukur kesenjangan kompetensi digital pada 12 indikator, dilanjutkan dengan Analisis Pareto untuk mengidentifikasi kompetensi kritis (vital few). Pada tahap kedua, lima kompetensi kritis dievaluasi oleh 9 panel ahli menggunakan metode Analytical Hierarchy Process (AHP) untuk menentukan prioritas akhir berdasarkan empat kriteria: urgensi, dampak kinerja, kesesuaian kebijakan, dan tingkat kesenjangan. Hasil TNA mengungkap kesenjangan tertinggi pada "Pengoperasian Aplikasi Spesifik" (gap -1,33) dan "Produksi Konten Digital" (gap -1,31). Analisis Pareto mengonfirmasi 78,4% total kesenjangan berasal dari lima kompetensi vital. Hasil AHP menunjukkan kriteria "Dampak pada Kinerja" menjadi determinan utama (bobot 40,1%). Sintesis prioritas global menghasilkan "Pengoperasian Aplikasi Spesifik" sebagai prioritas utama (bobot 0,397). Integrasi TNA dan AHP menghasilkan prioritas pelatihan yang lebih presisi untuk efektivitas alokasi sumber daya di era digital.   Kata Kunci: Penyuluh Perikanan; Kompetensi Digital; Training Needs Analysis; Analisis Pareto; Analytical Hierarchy Process